GE_GERICHTE C/6303/2013 vom 9. September 2016 - GE Cour de justice (2016)
EFFET SUSPENSIF ; ASSEMBLÉE DES COPROPRIÉTAIRES D'ÉTAGES ; ORDRE DU JOUR ; REPRÉSENTATION ; ABUS DE DROIT | CC.712.m.1.1; CO.32.1; CC.2.2;